Male genealogy study of the Iraqi Population - Halah Khalid Ibrahim Al-Sammarraie; Mohammed M. Al-Zubaidi; Asia Abdul lateef Mahdi (International Journal of Medical Toxicology and Legal Medicine, 2024)
The Y-chromosome of Short Tandem Repeats (STRs) plays a vital role in the field of forensics, particularly in the identification of male DNA in instances of sexual assault. Moreover, it is important in facilitating the connection of families through the application of genetic genealogy.In this study, the genetic polymorphisms of 23 Y-STR loci were analysed by the Power Plex® Y23 system in 383 healthy, unrelated male individuals randomly chosen from Iraqi populations. The result revealed 356 different haplotypes, including 337 unique haplotypes and 19 duplicate haplotypes. Two hundred and twelvedifferent genetic variants (alleles), were detected at which are distributed across 23 specific locations on the Y chromosome.The study examined the highest and lowest frequencies at each genetic locus and found that at the DYS392 locus, the microvariant allele "11" was the most common and widespread allele within the Iraqi population. The highest frequency of haplotype was 0.0098, which was found in samples H44, H70, H140, H206, and H255, while 337 haplotypes had 0.0033 frequencies, and haplotype diversity was 0.997 with a discrimination capacity of 0.946, respectively.The gene diversity values ranged from 0.395062 at DYS392 to 0.93828 at DYS385a/b. The Y-haplogroups of male Iraqi Arabs were determined using the NevGen Y-DNA Haplogroup online Predictor program. The most common haplogroups in this study were J1 (38%), J2 (20%), R1 (11%), E1 (10%), and G2 (5%). Although less common, additional predicted haplogroups were also discovered.The present study indicated that the 23 Y-STR loci were highly polymorphic in the Bagdad population and played crucial roles in forensic applications as well as population genetics. The study revealed the genetic diversity of male lineages in the Bagdad population using a high-resolution 23 Y-STR collection, and as a result, it’s contributed to familial research.